Electronic medical record–based tools aid in timely triage of disc‐shaped foreign body ingestions. (19th September 2018) - Lavin, Jennifer M.; Wiedermann, Joshua; Sals, Alexandra; Kato, Kimberly; Brinson, Dusty; Nytko, Agata; Katsogridakis, Yiannis; Krug, Steven; Ida, Jonathan
Abstract : Objectives/Hypothesis: Children presenting to the emergency department with coin‐shaped foreign body (FB) ingestion must be evaluated urgently to rule out a button battery. As many of these ingestions are well‐appearing on presentation, delays in triage put patients at risk for further injury. Study Design: Quality initiative. Methods: A quality initiative, utilizing electronic medical record (EMR)‐based tools, was implemented at our academic children's hospital. A chief complaint pertaining to coin‐shaped FB ingestion was created and was linked to a best practice advisory, instructing assignment of acuity level 2 and the order of a Stat x‐ray. A link to the hospital's relevant algorithm was provided. A review was conducted comparing children who underwent FB removal preinitiative (January 1, 2016–January 28, 2017) and postinitiative (January 31, 2017–August 30, 2017). Primary outcomes were frequency of assignment of acuity level 2 and time from patient arrival to x‐ray order placement and x‐ray completion. Results: Thirty‐six patients in the baseline group and 30 in the postintervention group underwent FB removal. The rate of appropriate acuity assignment increased from 63.8% (23/36) pre implementation to 100% (30/30) postimplementation ( P  = .0003). Median time from arrival to imaging ordered and completed decreased from 36.5 to 4 minutes (95% confidence interval [CI]: −44 to −17) and 59 to 41 minutes (95% CI: −39 to −1), respectively. Conclusions: Utilization of EMR‐based tools was associated with improved timeliness in initiation of care in metallic FB ingestion patients. Further initiatives will be aimed at downstream events in the diagnosis and treatment of these patients. Level of Evidence: NA Laryngoscope, 128:2697–2701, 2018